WOMEN AND SECONDARY SCHOOL PRINCIPAL ROTATION/SUCCESSION: A STUDY OF THE BELIEFS OF DECISION MAKERS IN FOUR PROVINCES - Reynolds, Cecilia; White, Robert; White, Robert; Brayman, Carol; Moore, Shawn (Canadian Journal of Education/Revue canadienne de l’éducation, 2008)
Our study investigated patterns of female participation as secondary principals that have varied across contexts and changed slowly. Researchers interviewed decision makers from a purposive sample of 10 urban and rural school districts in Ontario, Nova Scotia, Saskatchewan, and British Columbia, gathering data from structured telephone interviews, policy documents, and statistical information. The needs of a system took precedence over those of individuals. Many participants denied that gender influenced their rotation/succession practices; however, they identified differences by gender in leadership style and aspirations. Complex rules of control affected the participation of women as secondary principals. Gender clearly affects the participation of women as secondary school principals. Key words: gender, leadership, schools Les auteurs analysent les modes de participation de directrices d’école secondaire, lesquels varient d’un contexte à l’autre et changent lentement. Ils ont interviewé des décideuses provenant d’un échantillon choisi à dessein de dix arrondissements scolaires urbains et ruraux en Ontario, en Nouvelle‐Écosse, en Saskatchewan et en Colombie‐Britannique. Les données furent colligées au moyen d’entrevues téléphoniques structurées, le tout complété par l’analyse de documents de politiques et de renseignements statistiques. Leurs conclusions semblent indiquer que les besoins du système l’emportent sur les besoins de la personne. Un grand nombre des répondantes contestaient l’idée que le fait d’être un homme ou une femme exerce une influence sur les méthodes de rotation/succession ; elles notaient par contre des différences selon les sexes pour ce qui est du style de leadership, des orientations et des aspirations. Des règles complexes de contrôle affectent la participation des femmes à titre de directrices d’école secondaire. Le sexe affecte clairement la participation des femmes en tant que directrices d’école secondaire. Mots clés : genre, leadership, écoles